APPLICATION OF DIGITAL TECHNOLOGY FOR FABRICATING THE OBTURATOR IN REHABILATATION OF MAXILLARY DEFECT: A SYSTEMATIC REVIEW - Dr. Vikas Punia; Dr. Vaishnavi M. Ghuge; Dr. Anand Porwal; Dr. Abhijit Sethia; Dr. Palak Salgia (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Statement of problem - The purpose of this systemic review is to assess the outcomes of applications of digital technology for the fabrication of obturators in patients with maxillectomy defects. Digital techniques have been applied in dentistry to simplify oral rehabilitation procedures. The acquisition of 3 dimensional (3D) images of oral structures has made it possible to virtually define treatment planning, to design and mill restorations, and to monitor the result of surgical and restorative procedures. Material and methods- This study was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The protocol had been registered on PROSPERO (International Prospective Register of Systematic Reviews) with the registration number The PICOS (Population, Intervention, Comparison, Outcomes, and Study) criteria employed in the systematic review included. The focused question was “Applying digital technology and assessing the accuracy of obturators fabricated using digital techniques.” Inclusion criteria for this review was studies evaluating the rehabilitation of acquired maxillary defect using digital scanning methods. Conclusion- The main outcome of the review was that the application of digital workflows in the fabrication of obturators was found to reduce working time, minimize material consumption, and enhance patient comfort and acceptance.